MÔ HÌNH LÁT CẮT TỐC ĐỘ VỎ TRÁI ĐẤT VÀ TỐC ĐỒ THỜI GIAN TRUYỀN SÓNG ĐỊA CHẤN LÃNH THỔ VIỆT NAM - Lư, Ngô Thị (Vietnam Journal of Earth Sciences, 2017)
The new approach to specification of velocity model of earth's crust in the territory of Vietnam is developed and realized on the basis of new data about travel times of P-wave and velocity model of earth's crust. The algorithm for account of traveltimes of P-wave and simultaneous application of mathematical simulation of propagation of seismic waves was discussed. By comparison of experiment with theoretical hodographs, the specified approach was applied as an example insome variants to data of earthquakes of Vietnam.